Investigating the Combined Effect of Aerobic Training with Resveratrol Resveratrol Consumption on SIRT1 and PGC-1α Levels in Gastrocnemius Muscle of Rats after Spinal Cord Injury - Eskandar Garmei; Ali Yaghoubi; Najmeh Rezaeian (Journal of Mazandaran University of Medical Sciences, 2024)
Background and purpose: Atrophy of the skeletal system caused by spinal cord injury (SCI) can cause secondary systemic metabolic dysfunction, such as glucose intolerance, type 2 diabetes, and insulin resistance. On the other hand, Sirtun1 (SIRT1) and Peroxisome Proliferator-Activated Receptor-Gamma Coactivator-1alpha (PGC-1α) are known factors and related proteins involved in skeletal muscle atrophy. Therefore, the present study aimed to investigate the effect of aerobic training with resveratrol consumption on SIRT1 and PGC-1α levels in the gastrocnemius muscles of rats after spinal cord injury. Materials and methods: 36 male Wistar rats aged eight weeks were randomly placed in 4 groups including control, resveratrol, training, and resveratrol+training (each group n=9). After anesthesia, an incision was made in the midline of the back and over the vertebral ridges. The muscles and lamina of the T9 vertebra were removed without damaging the dura mater, Spinal cord injury was caused by dropping a ten-gram weight from a height of 25 mm on the spinal cord in the T10 segment. After confirmation of SCI, a Resveratrol supplement with a dose of 10 mg/kg was injected intraperitoneally and daily (every morning for 4 weeks), and the rats of other groups were injected with the same amount of saline. The aerobic training was carried out with the help of the weight support system for 4 weeks, 5 sessions per week, each session was 58 minutes and the intensity was 20 m/min. 48 hours after the last training session, the gastrocnemius muscle of right leg of all rats was removed. The SIRT1 and PGC-1α levels in the gastrocnemius muscle were measured by the ELISA method. To analyze the data, one-way analysis of variance and LSD post hoc tests were used at the significance level of P<0.05. Results: SIRT1 levels in the gastrocnemius muscle of resveratrol and resveratrol+training groups were significantly higher than the control group (P-value respectively 0.023 and 0.007), but despite the increase in the level of this index in the training group compared to the control group, no significant difference was observed (P=0.399). SIRT1 levels in gastrocnemius muscle of resveratrol+training groups were significantly higher than training group (P=0.038). PGC-1α levels in gastrocnemius muscle of training and resveratrol+ training groups were significantly higher than control group (P-value respectively 0.024 and 0.007), but despite the increase in the level of this index in the resveratrol group compared to the control group, no significant difference was observed (P=0.449). PGC-1α levels in gastrocnemius muscle of resveratrol+training groups were significantly higher than reveratrol group (P=0.023). Conclusion: These results show the positive effect of resveratrol consumption, on SIRT1 level, as well as aerobic exercise on PGC-1α level of the biceps muscle in rats with SCI. It has been pointed out that the increase in SIRT1 expression and the subsequent increase in PGC-1α leads to an increase in the number of myonuclei, which improves the recovery process after injury and plays an active role in muscle hypertrophy by upregulating and reducing catabolic processes. herefore, it appears that a combination of aerobic training and resveratrol supplementation can mitigate muscle atrophy caused by spinal cord injury in muscles below the level of injury by influencing the levels of muscle SIRT1 and PGC-1α